SKRINING STUNTING PADA ANAK USIA SEKOLAH DASAR DI WILAYAH KERJA PUSKESMAS SIMPANG KAWAT KOTA JAMBI - aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Harahap, Huntari (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACTStunting has long-term effects along children life time. Stunted children are at risk for growth disorders, intelligence, metabolic disorders, etc. Assessment and evaluation the impacts of stunting toddlers is very important to determine what policies will be carried out afterwards to deal with the problem. The purpose of this activity is to screen children with stunting in elementary schools in the working area of the Simpang Kawat Health Center in Jambi City. This activity held on August 10, 2023. The location of the activity carried out at State Elementary School 179 Jambi City, in the working area of the Simpang Kawat Health Center in Jambi City. This Community Service activities expected to help Simpang Kawat Health center for overcoming stunting by conducting screening, providing counseling and also providing multivitamins to elementary school-age children. From these results it can be seen that most of the participants 62% were women and 37.7% men. In the nutritional status examination based on BMI / U, students with underweight nutritional status were 11.47%, students with overweight nutritional status were 9.8% and normal nutritional status was 78.7%. In the examination of nutritional status based on TB / U, students with short stature results were 37.7% and students with normal results were 62.3%.Keywords: stunting, primary school age children, screening ABSTRAKAnak dengan stunting memiliki efek jangka panjang yang tidak sebaik anak normal, anak stunting berisiko untuk mengalami gangguan tumbuh kembang, kecerdasan, gangguan metabolic, dll. Penilaian dan evaluasi dampak apa yang telah terjadi pada balita Stunting sangat penting untuk dapat menentukan kebijakan apa yang akan dilakukan setelahnya untuk menangani masalah tersebut. Tujuan kegiatan ini adalah melakukan skrining anak-anak dengan stunting yang ada di Sekolah Dasar di Wilayah Kerja Puskesmas Simpang Kawat Kota Jambi. Kegiatan ini diselenggarakan pada tanggal 10 Agustus 2023. Lokasi kegiatan berada di Sekolah Dasar Negeri 179 Kota Jambi, di wilayah kerja Puskesmas Simpang Kawat Kota Jambi. Kegiatan Pengabdian Masyarakat ini diharapkan dapat membantu mitra dalam penanggulangan stunting dengan cara melakukan skrining, pemberian penyuluhan dan juga adanya pemberian multivitamin pada anak usia Sekolah Dasar. Dari hasil tersebut terlihat bahwa sebagian besar peserta 62% adalah perempuan dan 37,7% laki-laki. Pada pemeriksaan status gizi berdasarkan IMT/U siswa dengan status gizi underweight sebanyak 11,47%, siswa dengan status gizi overweight 9,8% dan status gizi normal adalah 78,7%. Pada pemeriksaan status gizi berdasarkan TB/U siswa dengan hasil perawakan pendek adalah sebanyak 37,7% dan siswa dengan hasil normal adalah 62,3%. Kata kunci: Stunting, Anak Usia Sekolah Dasar, Skrining